Prevention and Treatment of Tumor Lysis Syndrome in the Era of Onco-Nephrology Progress - Joanna Matuszkiewicz-Rowinska; Jolanta Malyszko (Karger Publishers, 2020)
Background: Tumor lysis syndrome (TLS) is an oncologic emergency due to a rapid break down of malignant cells usually induced by cytotoxic therapy, with hyperuricemia, hyperkalemia, hyperphosphatemia, hypocalcemia, and serious clinical consequences such as acute renal injury, cardiac arrhythmia, hypotension, and death. Rapidly expanding knowledge of cancer immune evasion mechanisms and host-tumor interactions has significantly changed our therapeutic strategies in hemato-oncology what resulted in the expanding spectrum of neoplasms with a risk of TLS. Summary: Since clinical TLS is a life-threatening condition, identifying patients with risk factors for TLS development and implementation of adequate preventive measures remains the most critical component of its medical management. In general, these consist of vigilant laboratory and clinical monitoring, vigorous IV hydration, urate-lowering therapy, avoidance of exogenous potassium, use of phosphate binders, and - in high-risk cases - considering cytoreduction before the start of the aggressive agent or a gradual escalation of its dose. Key Messages: In patients with a high risk of TLS, cytotoxic chemotherapy should be given in the facility with ready access to dialysis and a treatment plan discussed with the nephrology team. In the case of hyperkalemia, severe hyperphosphatemia or acidosis, and fluid overload unresponsive to diuretic therapy, the early renal replacement therapy (RRT) should be considered. One must remember that in TLS, the threshold for RRT initiation may be lower than in other clinical situations since the process of cell breakdown is ongoing, and rapid increases in serum electrolytes cannot be predicted.